Financial technology, financial knowledge, and financial attitude of Generation Z: Determinants of financial behavior - Febrio Andi Prasetyo; Mustaqim Mustaqim (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The aim of this study is to examine the influence of financial technology, financial literacy, and financial attitudes on the financial behavior of Generation Z within the framework of Society 4.0.Method — This quantitative descriptive research utilizes a questionnaire-based data collection approach distributed online through Google Forms to university students in Sidoarjo. A total of 94 responses were gathered from the questionnaire distribution. Subsequently, to discern the individual impacts, the data from the questionnaire were subjected to analysis employing t-tests and multiple linear regression using SPSS version 2.1.Result — This study reveals that financial technology has an influence on the financial behavior of college students, while financial literacy affects their financial behavior. Additionally, financial attitudes also impact their financial behavior.Practical implications — This study suggests a pressing need for educational institutions to enhance financial education programs, integrating concepts from behavioral finance and emphasizing practical application, to improve students' understanding of financial behavior and decision-making for effective personal financial management.